Penguatan Pendidikan Karakter Melalui Pembelajaran Agama Islam Interaktif di Sekolah Dasar - Sitto Rahmana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Islamic religious education (PAI) in elementary schools plays a very important role in shaping students' character from an early age. One of the basic materials that needs to be given to students is about morals and ethics in Islam. Through teaching good morals, it is hoped that students can understand and apply the moral values ​​taught in Islam in everyday life. This community service aims to provide a deeper understanding of morals and ethics in Islam to elementary school students, especially those related to noble behavior, such as honesty, patience, helping each other, and respecting others. This community service activity is carried out through the use of visual and audiovisual media to facilitate students' understanding. In this activity, students are invited to learn through inspirational stories in Islam, and are given the opportunity to discuss and practice good behavior in accordance with the teachings of Islam. It is hoped that with this fun and interactive approach, students can internalize moral values ​​in their lives. Through this community service, it is hoped that students will not only gain knowledge about Islamic morals, but can also apply them in their daily social interactions. In addition, this activity also aims to strengthen collaboration between schools, students, and the community in creating a generation with noble morals and high integrity. The results of this activity are expected to provide a positive contribution in developing the character of students in elementary schools, as well as being a model for moral teaching activities in other schools.